Job Satisfaction And Work Life Balance Among Female Employees: A Study In Public Sector Univercity In Bhilwara City - Deepti Rustagi; Akhil Goyal (International Journal of Psychosocial Rehabilitation, 2020)
Most people’s life revolve heavily on their jobs. Work, whether paid or unpaid, helps us maintain our sense of self and our sense of purpose in life; it allows (or requires) us to divide up our time in a productive manner; it provides us with something to show for our time each day; it raises our social standing and that of our families and communities; and it introduces us to new people. What we mean when we talk about striking a "work life balance" is describing the interplay between one’s professional responsibilities and their personal obligations. Work-life balance issues are a common cause of tension for people in modern society. When discontent with one’s job becomes severe, decisive action is required. Finding a happy medium between one’s professional and personal commitments is essential to achieving work-life balance. A company’s performance ultimately depends on the efforts of its employees, which may be influenced by several factors. Researching the effects of stress and work-life balance on employee satisfaction in the workplace, empirical research was undertaken among women at public-sector banks.